Efektivitas Campuran Daun Sirih Hijau dan Merah Sebagai Obat Kumur terhadap Jumlah Bakteri dan Plak Gigi: Studi Perbandingan - Budi Suryana; Damhuji Damhuji; Dian Femala; Halimah Halimah (Universitas Pahlawan Tuanku Tambusai, 2025)
Mouthwash is a solution used to clean the oral cavity to eliminate bacteria. Green and red betel leaves are believed to contain higher phenol content, which can inhibit bacterial activity. The purpose of this study is to determine the difference in effectiveness of a mixture of green and red betel leaf decoction as a mouthwash in reducing bacterial counts and plaque scores. This research is a quasi-experiment with a pretest and posttest controlled group design. The population consists of students from the Dental Nursing Department using purposive sampling technique, totaling 69 students divided into three groups, each with 23 samples using green betel leaf, red betel leaf, and a mixture of both decoctions as mouthwash. Effectiveness was tested with paired t-test, while differences were analyzed using Kruskal-Wallis and Mann-Whitney tests. The results showed that mouthwash with green betel leaf, red betel leaf, and a mixture of both decoctions were effective in reducing bacterial colonies and plaque on teeth. There were significant differences in reducing bacterial colonies among the three types of decoctions, but no differences in reducing plaque scores. The use of mouthwash from betel leaf decoctions is a good protective measure with easily obtainable and applicable materials for the community to avoid the use of chemical substances.